Automatic classification of carbonate rocks permeability from 1H NMR relaxation data. Issue 9 (1st June 2015) - da Silva, Pablo Nascimento; Gonçalves, Eduardo Corrêa; Rios, Edmilson Helton; Muhammad, Asif; Moss, Adam; Pritchard, Tim; Glassborow, Brent; Plastino, Alexandre; Azeredo, Rodrigo Bagueira de Vasconcellos
Highlights This work investigates the effectiveness of data mining analysis on NMR data. The goal is to accurately predict the permeability class of carbonate rocks. Our approach outperforms the traditional NMR models Timur–Coates and Kenyon. Traditional models ignore the singular relationship between T2 bins and pore throat. Data mining models capture the influence of each T2 bin over the permeability class.